1985
DOI: 10.1113/jphysiol.1985.sp015865
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulation of hind‐limb blood flow in conscious dogs.

Abstract: SUMMARYt. We evaluated the efficiency of blood flow autoregulation of the hind-limb vascular bed of eleven conscious dogs during: (a) resting conditions; (b) graded levels of treadmill exercise; and (c) increases in oxygen consumption produced by the administration of 2,4-dinitrophenol (DNP).2. Blood flow to the left hind limb was measured with an electromagnetic flow probe on the left external iliac artery. Hind-limb perfusion pressure was measured from a catheter in the deep femoral artery and was controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the results of our investigation suggest that the effect of an increase in vasomotor tone (tending to decrease blood flow) from chemoreceptor stimulation can be reversed passively by a rise in blood pressure in the muscle bed but not in the renal bed. This difference in the effects in two vascular beds may be related to the difference in autoregulatory phenomenon, which is absent in resting muscle (Britton et al 1985), and very prominent in the kidney (Johnson, 1986). An increase in muscle blood flow, therefore, does not necessarily mean inhibition or withdrawal of the sympathetic vasoconstrictor tone as claimed by Hilton & Marshall (1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results of our investigation suggest that the effect of an increase in vasomotor tone (tending to decrease blood flow) from chemoreceptor stimulation can be reversed passively by a rise in blood pressure in the muscle bed but not in the renal bed. This difference in the effects in two vascular beds may be related to the difference in autoregulatory phenomenon, which is absent in resting muscle (Britton et al 1985), and very prominent in the kidney (Johnson, 1986). An increase in muscle blood flow, therefore, does not necessarily mean inhibition or withdrawal of the sympathetic vasoconstrictor tone as claimed by Hilton & Marshall (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Since the response of the cutaneous veins to chemoreceptor stimulation is a vasodilatation (Calvelo, Abboud, Ballard & Abdel-Sayed, 1970;Koike, Mark, Heistad & Schmid, 1975), it is not certain whether the vasodilatation of the whole limb was the result of the effect of chemoreceptors on the venous system, or due to the increase in systemic arterial pressure which was not controlled in the experiments of Marshall (1981Marshall ( , 1987 and Hilton & Marshall (1982). An increase in systemic arterial pressure can mechanically raise the flow, particularly when autoregulation in the muscle vascular bed is absent in the resting condition (Britton, Metting, Ronau, Strader & Weldy, 1985).…”
mentioning
confidence: 99%
“…Autoregulation of blood flow is absent or weak in resting skeletal muscle (23), and the cutaneous circulation is generally described as a passive vascular bed (24). Because systemic vascular autoregulation results from the net autoregulatory contribution of all of the regional vascular beds, redistribution of blood flow from A number of studies have shown that the effectiveness of autoregulation is enhanced when tissues operate near their nutritive limit (12,14,23,25); only vasopressin caused a significant decrease in baseline cardiac output (Table I), which would bring tissues closer to this limit. This may be another reason for finding a greater contribution of autoregulation in the hemodynamic response to vasopressin compared to angiotensin II or norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Outputs from Doppler flow channels were recorded in kilohertz of Doppler frequency shift. Calibration of the flow probes was performed in situ at the completion of all experiments while the animals were anaesthetized (Britton, Metting, Ronau, Strader & Weldy, 1985). Alternatively, the flow in ml min-' was calculated using the Doppler equation (Ishida, Lewis, Hartley, Entman & Field, 1983).…”
Section: Mea8urementsmentioning
confidence: 99%